The Uttermost Farthing: A Savant's Vendetta - Freeman, R. Austin (Richard Austin), 1862-1943 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Uttermost Farthing: A Savant's Vendetta" by R. Austin Freeman is a novel likely written during the early 20th century. The story revolves around Humphrey Challoner, a brilliant but troubled savant whose life takes a dark turn following the tragic murder of his wife. Known for his expertise in criminal anthropology, Challoner becomes consumed by his desire for retribution against his wife's murderer, leading to chilling and morally complex decisions that intertwine science with vengeance. The opening of the novel introduces the reader to the backstory of Challoner through the reflective account of his friend, Dr. Wharton. It establishes Challoner as an eccentric and brilliant character, once renowned in his field, who has turned his private museum into a crypt of his memories and tragedies. In this narrative, Challoner reveals his warped moral compass shaped by grief as he prepares to confront the criminal world and collect a "debt" from the murderer. The startling details of his collection, including human skeletons and gruesome artifacts, set a macabre tone that hints at the psychological and ethical dilemmas Challoner will face as the story unfolds. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by Steven desJardins and Distributed Proofreaders
Keywords: Mystery and detective stories; Vigilantes -- Fiction